n, n + 2, n + 4 - three consecutive even integers
the twice the sum of the second and third: 2[(n + 2) + (n + 4)]
twelve less than six times the first: 6n - 12
The equation:
2[(n + 2) + (n + 4)] = 6n - 12
2(n + 2 + n + 4) = 6n - 12
2(2n + 6) = 6n - 12 <em>use distributive property</em>
(2)(2n) + (2)(6) = 6n - 12
4n + 12 = 6n - 12 <em>subtract 12 from both sides</em>
4n = 6n - 24 <em>subtract 6n from both sides</em>
-2n = -24 <em>divide both sides by (-2)</em>
n = 12
n + 2 = 12 + 2 = 14
n + 4 = 12 + 4 = 16
<h3>Answer: 12, 14, 16</h3>
Answer:
look at the picture i have sent
Answer:
xy = -1 and y = -1/x are the same.
They are not linear equations because they are not written in the form
Ax + By = C.
The answer is C because it is on the x axis and it is positive
The second graph: y = 3
Domain: all real number
Range: y = 3